Kinerja Karyawan Industri Manufaktur Perkayuan Kaitannya dengan Kelelahan Kerja (Burnout) dan Disiplin Kerja. - Gunawan, Muhammad Taufik S; Sumiyati, Sumiyati; Masharyono, Masharyono (Universitas Pendidikan Indonesia, 2017)
Objective of this research is to determine the effect of burnout and work discipline on employee performance. This research was conducted in a span of less than one year, so the research design used was a cross-sectional method. This study uses a descriptive and verification approach with explanatory survey methods. A total of 100 respondents were selected as samples using probability sampling. The research questionnaire is used as a research instrument to collect data from respondents, and the data analysis technique used is multiple linear regression. The findings of this research is work fatigue (burnout) and work discipline have a significant influence on employee performance.Â Differences found in objects and research methods, population and research samples, research periods, measurement tools and research results, and sources of theory from foreign journals and foreign books